Inequality gaps in modern contraceptive use and associated factors among women of reproductive age in Nigeria between 2003 and 2018 - Obasanjo Afolabi Bolarinwa (BMC, 2024)
Abstract Background Inequalities in modern contraceptive use among women in low-income countries remain a major public health challenge. Eliminating or reducing the inequalities in modern contraceptive use among women could accelerate the achievement of Sustainable Development Goals, Targets 3.7 & 5.6. Thus, this study examined the inequality gaps in modern contraceptive use and associated factors among women of reproductive age in Nigeria between 2003 and 2018. Methods This study employed the World Health Organisation's Health Equity Assessment Toolkit to analyse the 2003 and 2018 Nigeria Demographic Health Surveys. Modern contraceptive use was aggregated using five equity stratifiers: age, economic status, educational level, place, and region of residence among women of reproductive aged 15 to 49, with a sample size of 5,336 and 29,090 for 2003 and 2018, respectively. Inequality was measured in this study using difference (D), ratio (R), population-attributable risk (PAR), and a population-attributable fraction (PAF). Results The study shows an increase in modern contraceptive use among women of reproductive age in Nigeria from 8.25% in 2003 to 12.01% in 2018, with the use being more prominent among women of reproductive age 20-49 and those in the richest economic quintile. In both surveys, women with primary education showed the most upward increase in modern contraceptive use. Women residing in the urban areas also show an upward use of modern contraceptives use. The study further highlights inequality gaps, with age being a substantial factor, while economic status and sub-national regions showed mild to marginal inequality gaps. Finally, the educational level of women of reproductive age in Nigeria significantly shows inequality in modern contraceptive use, with a PAF of 129.11 in 2003 and 65.39 in 2018. Conclusion The inequality gap in modern contraceptive use among women of reproductive age in Nigeria between 2003 and 2018 reported in this study includes age, education, wealth quintile, residence, and region-related inequalities. The study highlights the need for policies and programmes that target the groups with low use of modern contraceptives to promote equity in family planning services.